Chronic obstructive pulmonary disease (COPD) related to wood smoke: an analytical sociodemographic, clinical, functional, imaging, and biomarkers profile characterization in comparison with tobacco smoke COPD. (2024)
Around 40 percent of the world population, that is 2.8 billion people, continues using solid fuels (charcoal and biomass: wood, dung, crop) for cooking or home heating (1-3). Chronic exposure to biomass fuel smoke, particularly wood smoke, has been identified as a significant risk factor for various respiratory conditions, including respiratory infections in children, chronic bronchitis, asthma, and chronic obstructive pulmonary disease (COPD) (4-7). These conditions are of great global concern, given their high prevalence, substantial morbidity and mortality rates (8).